PROTOTIPE ‘PENYULUH AGAMA BUDDHA’ KAJIAN LINGUISTIK KOGNITIF: (Prototype of ‘Penyuluh Agama Buddha’: A Cognitive Linguistics Study) - Prasetyo, Lery; Abbas, Asriani; Benu, Naniana N (Uniqbu Journal of Social Sciences, 2022)
Prototype in linguistics field is a mean to determine the level of meaning gradations, where the people have their own concepts, models or views on something. This is a descriptive qualitative research supported by quantitative data. The results show that the most important component of prototype of ‘Penyuluh Agama’ is moral according to the concept of sila (morality) as the basis of Buddha’s teaching implementation. In addition, the prototype of ‘penyuluh agama Buddha’ is based on including two variables, gender, and council.. The two variables have different perspectives and influences on the prototype of ‘penyuluh agama Buddha’. However, most consider the moral component as the most important component. Moreover, the component of the same council is also considered important.